Recuperação de cério e lantânio lixiviados de fosfogesso por adsorção utilizando resíduos de uva - Silva, Rafaela Nogueira Fontoura da (2023)
Phosphogypsum is a byproduct of the fertilizer industry with a high environmental impact, formed during the production of phosphoric acid from phosphate rock. It mainly comprises gypsum and may contain impurities, including earth elements (ETRs). A favorable alternative for managing this material is the recovery by adsorption of REEs leached from phosphogypsum. Adsorption using industrial waste as adsorbents is even more promising. Within this context, grape residue originates from obtaining wine, and its disposal can also cause environmental consequences due to its high concentration of phenolic compounds. Thus, the present research aimed to evaluate the use of grape stalk in the adsorption of lanthanum and cerium to identify the best operating conditions enabling the application of the bioadsorbent in ETRs leached from phosphogypsum. The grape stalk was characterized and showed an amorphous structure with a heterogeneous and very porous surface. Also, it was possible to identify the groups corresponding to carboxylic acids, phenols, alcohols, aliphatic acids, and aromatic rings. The pH effect study showed that the adsorption process of La3+ and Ce3+ ions was favored at pH 5.0. The adsorption kinetics followed the pseudo-second-order model. In just 20 minutes, 80% saturation was reached, while equilibrium was reached after 120 minutes. The adsorption isotherms were appropriately adjusted to the Langmuir model, and the maximum adsorption capacities were obtained at 298 K, which were 35.22 mg g-1 for La3+, and 37.99 mg g-1 for Ce3+. Furthermore, the adsorption process was favorable, spontaneous, and exothermic. In the study's second phase, phosphogypsum was leached with a sulfuric acid solution. Then, the adsorption of ETRs was carried out under the experimental conditions of pH after leaching and pH 5.0 (adjustment carried out with sodium hydroxide solution) at 298 K for 120 min and with adsorbent dosages of 1 and 5 g L-1 . This process resulted in removal percentages above 95% for the most abundant REEs, such as neodymium, lanthanum, and cerium, at pH 5.0 and a dosage of 5 g L-1 , demonstrating the effectiveness of the bioadsorbent used. These results indicate the potential of using grape residue as a promising bioadsorbent in recovering rare earth elements from phosphogypsum leachate.